Global community? : transnational and transdisciplinary exchanges - Enroth, Henrik; Brommesson, Douglas (Rowman and Littlefield International, 2015)
Explores the range and depth of work currently being done in the humanities and social sciences on the conceptual, normative and empirical aspects of global community.